Responses of terrestrial plants and invertebrates to environmental change at high latitudes - Callaghan, Terry V.; Sonesson, Mats; Sømme, Lauritz; Walton, D. W. H.; Christensen, T.; Block, W. C.; Drewry, D. J.; Laws, Richard Maitland; Pyle, John Adrian (Philosophical Transactions of the Royal Society of London. Series B: Biological Sciences, 1997)
Many invertebrates show flexibility in their life cycles and are likely to respond to changes in climate as they have in the past. However, changes in temperature and photoperiod may disturb the life cycles of some existing polar invertebrates while continuing to constrain the polewards migration of more temperate species. Higher plants are likely to have higher productivity as temperatures and atmospheric CO2 levels increase but this productivity will be reduced by exposure to increasing UV-B radiation. Higher plants migrate more slowly than the rate at which climate is predicted to change and many species will be trapped in supra-optimal climates. Both mosses and lichens can migrate faster than higher plants, propagules of non-polar species already reaching the Antarctic, but they have fewer mechanisms of responding to changing environments. Polar vegetation and ecosystems provide feedback to the climate system: positive feedbacks are associated with decreases in reflectivity and increased carbon emissions from warm ing soils. In the Antarctic, feedback and responses to environmental change will be smaller than in the Arctic because of the less responsive cryptogams which dominate the Antarctic, the paucity of Antarctic soils, and geographical barriers to plant and invertebrate migrations.
Publisher: Royal Society
Keywords: Antarktis; biologi; botanikk; klimaendringer; lav; moser; virvelløse dyr

Anhydrobiosis and cold tolerance in tardigrades - Sømme, Lauritz (European Journal of Entomology, 1996)
A review of the literature regarding anhydrobiosis and cold tolerance in tardigrades is presented. During increasing desiccation, invertebrates like tardigrades, rotifers, nematodes and some collembolans are able to shut down metabolism to undetectable levels. When tardigrades are entering anhydrobiosis, a tun-like structure is formed, facilitated by structural adaptations of the cuticle. Slow dehydration is essential for tun formation, and the accumulation of trehalose during this process may help to stabilize phospholipids and proteins. Wax extrusion on the cuticle surface reduces transpiration. A fraction of 5-15% of the initial body water is retained during anhydrobiosis. Tardigrades are principally aquatic organisms, but anhydrobiosis makes it possible for some species to live in habitats with changing moisture conditions. Tardigrades in anhydrobiosis may tolerate exposure to freezing temperatures of liquid gases, and some species also survive such temperatures in their hydrated state. Few investigations are available on the relation of tardigrades to temperatures more representative to their natural environments. Experimental studies, however, from Greenland and the Antarctic Continent suggest that some species overwinter both in a hydrated frozen state and in anhydrobiosis. During the summer, a number of tardigrade species have been recorded from cryoconite holes, formed on the surface of glaciers. These species are freeze tolerant since their habitats are permanently frozen during the winter.
Keywords: Antarktis; Dronning Maud Land; biomonitorering; bjørnedyr; entomologi; kuldetoleranse; polarområdene; virvelløse dyr

Invertebrates in Hot and Cold Arid Environments - Sømme, Lauritz (Springer-Verlag, 1995)
Keywords: Antarktis; forskning; kuldetoleranse; virvelløse dyr

Cold tolerance in Tardigrada from Dronning Maud Land, Antarctica - Sømme, Lauritz; Meier, Terje (Polar Biology, 1995)
Survival at low temperatures was studied in three species of Tardigrada from Muhlig-Hofmannfjella, Dronning Maud Land, Antarctica. Both hydrated and dehydrated specimens of Echiniscus jenningsi, Macrobiotus furciger and Diphascon chilenense had high survival rates following exposure to -22 degrees C for ca. 600 days, and dehydrated specimens following 3040 days at this temperature. In hydrated E. jenningsi, mortality increased with the duration of exposure from 7 to 150 days at -80 degrees C, while mortalities of the two other species did not change. Hydrated specimens of all species were rapidly killed at -180 degrees C, but all species exhibited good survivorship in the dehydrated state after 14 days at -180 degrees C. In conclusion, hydrated tardigrades are able to survive extended periods at low temperatures, and dehydrated specimens are even better adapted to survive overwintering on Antarctic nunataks.
Keywords: Dronning Maud Land; biologi; biomonitorering; bjørnedyr; kuldetoleranse; virvelløse dyr

Notes on the ecology and physiology of the Antarctic oribatid mite Maudheimia wilsoni - Sømme, Lauritz; Strømme, Alexander; Zachariassen, Karl Erik (Polar Research, 1993)
The oribatid mite Maudheimia wilsoni Dalenius was found to be numerous on the underside of stones at Jutulsessen (72-degrees-S, 3-degrees-E) in Dronning Maud Land, Antarctica. Daily temperature fluctuations of the microhabitat from as high as 19-degrees-C and to as low as -17-degrees-C were observed during the austral summer. Optimal activity of the mites occurred at 10-degrees-C. Even in January the mean supercooling point of adult mites was as low as - 30.8 +/- 4.7-degrees-C. Haemolymph osmolality ranged from 500 to 800 mOsmol and thermal hystersis freezing points from -4.7 to - 6.1-degrees-C. Adult mites had a mean water content of 43.6% and a water loss rate of 0.12 mug h-1 at 15-degrees-C and 10% relative humidity.
Keywords: Dronning Maud Land; NARE 1989/90; entomologi; midder; miter; virvelløse dyr; zoologi; økofysiologi; økologi

Ecophysiological adaptations in mites and collembolans in Dronning Maud Land - Strømme, Alexander (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; midder; miter; virvelløse dyr; zoologi; økofysiologi